A Translation Study of the Meaning and Aesthetics of Drama Subtitles of When We Were Young (人不彪悍枉少年) as Literary Works on WeTV Channel Indonesia: A Review of Literary Translation Theory - Siregar, Sheyra Silvia; Marsuki, Ria Riski; Siregar, Sheyla Silvia (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
This study aims to analyze the translation of the meaning and aesthetics of the subtitles of the drama When We Were Young (人不彪悍枉少年) aired on the YouTube channel WeTV Indonesia, as well as discuss the translation of this drama as a literary work. The main focus of this study is to understand how the translator overcame linguistic and cultural challenges in translating the dialog-drama which is full of Chinese idioms and cultural expressions into Indonesian. This research uses a descriptive qualitative approach with a case study design to analyze the subtitle texts. The data used are purposively selected drama subtitles from several episodes that contain idiomatic and metaphorical elements. Literary translation theories, such as equivalence theory by Nida (1964), domestication vs. foreignization theory by Venuti (1995), and audiovisual translation theory by Gottlieb (1994), are applied in this analysis to explore how translators balance between fidelity to the source text and the limitations of subtitle space. The study found that translators often adopt a domestication approach to ease the understanding of Indonesian audiences, while still trying to maintain the original aesthetics and cultural nuances of the source text. The findings make an important contribution to the study of literary translation, especially in the context of audiovisual translation which requires attention to linguistic and cultural aspects simultaneously.